The growth of mathematical imagination of students of a deaf school when learning using Problem-Based Learning assisted by manipulative teaching aids - Ni'mah, Lailatun; Sugiman, Sugiman (Department of Mathematics, Universitas Negeri Semarang, 2020)
The ability of mathematical imagination is important in daily life for children with deaf disabilities. One effort to foster mathematical imagination is through a problem-based learning model assisted by manipulative props. This study aimed to: (1) find out whether the results of the mathematical imagination final test of deaf students with the application of the Problem-Based Learning assisted by manipulative props are better that the results of the initial test; (2) describe the mathematical imagination of the deaf students; (3) find out the growth of mathematical imagination of the deaf students. This research was mixed-method research that used a sequential exploratory design with a one-group pretest-posttest design. The population of this research was the students of a special school for disabilities (SMALBN) in Salatiga, Indonesia, while the sample was a random class from the 11th classes. The method used in this research were observation, documentation, tests, and interviews. Quantitative analysis showed that the final test of mathematical imagination result was better than the results of the initial test. Qualitative analysis yield a description of mathematical imagination that included aspects such as scientific sensitivity, scientific creativity, and good scientific productivity. The scientific sensitivity aspect of the imagination growth before learning was good, and the scientific creativity aspect was quite good. After learning, it was obtained that scientific sensitivity, scientific creativity, scientific productivity were good. The study concluded that problem-based learning assisted by manipulative props could foster the ability of mathematical imagination of deaf students in 11th grade.